Depletion and inventory calculation for the new fuel of IEN's Argonauta reactor - Iago Gomes; Victor Lassance; Maria de Lourdes Moreira (Brazilian Journal of Radiation Sciences, 2025)
This paper presents fuel depletion simulations for the Argonauta research reactor using the MCNP6® 1.0 code. The actinide fission yield inventory for the reactor's current U3O8 fuel was conducted from 1965 to 2018 using operating parameters obtained from a previous study. Inventories were also generated for hypothetical scenarios involving the reactor's new fuel under development (U3Si2). The U3Si2 analysis indicated a mass increase for all highlighted actinides across the hypothetical scenarios. Regarding fission product yields, results showed that after 20 years of operation at 1000 W (the new estimated operating power), the mass of all highlighted isotopes was higher than for the same period at 340 W (the current power). These findings are relevant for licensing procedures of the new fuel and for assessing potential accident scenarios, since transitioning to U3Si2 fuel and increasing reactor power may impact the isotopic inventory.